MORPHOMETRIC AND VOLUMETRIC CBCT ANALYSIS OF THE ORBITS IN PATIENTS FROM NORTH-EASTERN PART OF ROMANIA - Ana Sîrghie; Sorin Axinte; Andrei Costea; Anca Ignat; Ana Nemtoi; Diana Madalina Gucianu; Ruxandra Vatavu; Chirica Sabina Ioana; Alexandru Nemtoi (Romanian Society of Oral Rehabilitation, 2024)
Purpose: The purpose of this study was to determine cone-beam computed tomography (CBCT) as a tool for measuring morphometric and volumetric measurements of the orbit. Patients and methods: Morphometric and volumetric values of 100 orbits (50 subjects, 21 men/29 women) were measured using CBCT. Their mean and standard deviation were measured and analyzed. The measurement were realized using two imaging diagnosis softwares: Romexis and Radiant. Results: CBCT could accurately measure the various morphometric and volumetric parameters of the orbit. The results obtained from the measurement of parameters on CBCT in specific sections at both orbits are: the mean cranio-caudal diameter of the orbit was 38.2 mm, the mean transverse diameter of the orbit was 34.22 mm, the average of the antero-posterior diameter of the orbit was 47.41 mm, the average orbital volume was 83.55 cm3. The maximum and mean value of the left antero-posterior diameter in the axial plane was higher when measured with the RadiAnt program, while the minimum value showed a higher result when measured with Romexis. Conclusion: CBCT is an important viable tool for morphometric and volumetric measurements of the orbit and other craniofacial structures. It can also assess age and gender variability. The low cost, high accuracy, low radiation, and ease of use can help in reproducibility among the different living populations.